The Application of Video Media to Increase Student Motivation and Learning Autcomes in Flat Sided Space (Prism) Material in Class VIII SMPN 2 Pasir Limau Kapas Odd Semester of The 2021-2022 Academic Year - Siregar, Erlina (Journal of General Education Science, 2024)
This research aims to increase student motivation in the learning process of building flat-sided spaces about Building Flat-sided Spaces (Prisma) in class VIII students at SMP Negeri 2 Pasir Limau Kapas Semester I of the 2021/2022 academic year. This research was conducted because of student motivation in learning about flat-sided spatial construction about flat-sided spatial construction (Prisma) in class VIII students at SMP Negeri 2 Pasir Limau Kapas Semester I of the 2021/2022 academic year. still relatively lacking. The research subjects were 20 students in class VIII of SMP Negeri 2 Pasir Limau Kapas Semester I of the 2021/2022 academic year. The procedures for carrying out actions and implementation at the research location are divided into 2 cycles. Each cycle consists of four stages, namely: planning, acting, observing and reflecting and is carried out in 4 meetings. Data collection techniques use tests, observations, and documentation of learning activities. Analysis is carried out using techniques data analysis qualitative and technique analysis data qualitative. Results this research shows that the use of the PjBL learning model with video media in learning to build a flat-sided room, material on building a flat-sided room (Prism) capable improve skills students in making innovative works of prism nets in class VIII of SMP N 2 Pasir Limau Kapas Semester I Academic Year 2021/2022.